The Influence of Learning Concentration on Preschool children Learning Outcomes - Budiwanto, Adri; Marheni, Eddy; Ihsan, Nurul; Pranoto, Nuridin Widya; Purnomo, Eko (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the effect of concentration on the learning outcomes of early childhood students, specifically in physical education. Using the Causal Comparative Research method, this study compares two groups of students with different concentration levels to observe the differences in their learning outcomes. The data collected were analyzed using statistics, including the t-test, with a significance level 0.05. The results show that students with higher levels of concentration showed significant improvement in learning outcomes compared to students with lower levels of concentration. The coefficient of determination of 25.1% indicates that learning concentration contributes to sports learning outcomes, while 74.9% is influenced by other variables not examined in this study. Â These findings emphasize the importance of concentration in supporting the development of physical and cognitive skills in young children. The implications of this study suggest the need for teaching strategies that can enhance students' concentration, such as structured physical activities and more interactive learning. This research provides insights for educators to develop more effective teaching methods to improve concentration and learning outcomes in early childhood education.